Salt tolerance in Argentine weathgrass [Elymus scabrifolius (Döll) J.H. Hunz.] is related to shoot sodium exclusion - Zabala, Juan Marcelo (2020)
This is the first report about Na and K fluxes and heritability of Na exclusion in the Elymus genus. Argentine wheatgrass (Elymus scabrifolius ) is an important forage genetic resource for saline environments. A previous study had shown salt‐sensitive lines accumulated toxic levels of Na in shoots. The aim of this study was to increase the understanding of Na exclusion in Argentine wheatgrass. Growth and Na and K accumulation rates were analyzed in two homozygous salt‐tolerant genotypes (T1 and T2) and a salt‐sensitive one (S1), under different salt stress levels. The Na accumulation rate in shoots was 1.5 times higher in the sensitive line than in the tolerant ones at 100 mM NaCl, and 5 times higher at 200 mM NaCl. A negative association was found between Na concentration and leaf weight in parent genotypes, F1 and segregating F2 population generated by crossing homozygous S1 and T2, suggesting that growth in the third leaf was more affected in Na‐including genotypes. The inheritance of Na exclusion was estimated under salt stress conditions in a segregating F2 population and in F2:3 families obtained by crossing two homozygous genotypes with contrasting values of shoot sodium exclusion. In F2 population and F2:3 families, Na concentration segregation was compatible with intermediate inheritance (with very low partial dominance). High heritability values estimated for Na exclusion suggest that this trait might be used as a priority selection criterion for salt tolerance. Results will be useful to design breeding strategies for salt tolerance in this and related species of the Elymus genus.